Foliar tissue degradation in Elymus breviaristatus subsp. scabrifolius and E. scabriglumis (Gramineae) - Nuciari, M. C. (Agrociencia Uruguay, 2008)
Foliar tissue degradation in Elymus breviaristatus subsp. scabrifolius and Elymus scabriglumis was characterized at vegetative and reproductive stages during 24, 48 and 72 h of in situ digestion and degradation rate was estimated. Tissue degradation pattern in studied species presented similar information reported for temperate C3 plants. Parenchyma and chlorenchyma means were 80.2 and 29 % for both main tissues when estimated in E. breviaristatus subsp. scabrifolius, at 72 h of digestion time, and 86.5 and 29.5 % in E. scabriglumis, respectively. Degradation rates of chlorenchyma and xylem were different according to leaf part. Xylem degradation rate was similar between blades of both species. Also chlorenchyma and phloem degradation rates were different according to leaf parts and developmental stages. Differences in biodegrability found should be explained by quality and quantitative tissue characteristics. Results suggest that E. scabriglumis should be a valuable resource in The Flooding Pampa Area at periods of limited supply forage.